2016
DOI: 10.3386/w22344
|View full text |Cite
|
Sign up to set email alerts
|

Labor Supply Effects of Occupational Regulation: Evidence from the Nurse Licensure Compact

Abstract: There is concern that licensure requirements impede mobility of licensed professionals to areas of high demand. Nursing has not been immune to this criticism, especially in the context of perceived nurse shortages and large expected future demand. The Nurse Licensure Compact (NLC) was introduced to solve this problem by permitting registered nurses to practice across state lines without obtaining additional licensure. We exploit the staggered adoption of the NLC to examine whether a reduction in licensure-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In contrast, we focus on a profession providing highly tradable services for which geographic barriers may impose greater costs. As such, our findings complement those of DePasquale and Stange [2016] and suggest that licensing‐induced geographic costs are especially relevant when services are highly tradable (Crino [2010], Criscuolo and Garicano [2010]).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, we focus on a profession providing highly tradable services for which geographic barriers may impose greater costs. As such, our findings complement those of DePasquale and Stange [2016] and suggest that licensing‐induced geographic costs are especially relevant when services are highly tradable (Crino [2010], Criscuolo and Garicano [2010]).…”
Section: Introductionsupporting
confidence: 85%
“…Geographic barriers are believed to be one of the most severe costs imposed by occupational licensing regulations (e.g., Kleiner [2000]), yet no compelling empirical evidence supports this claim. DePasquale and Stange [2016] investigate the impact of such restrictions on the labor market for nurse practitioners and find no evidence of wage effects, suggesting that the potential costs of geographic barriers are not severe. However, their results may hinge on the low tradability of healthcare services that naturally require face‐to‐face provision (Crino [2010]).…”
Section: Introductionmentioning
confidence: 99%
“…This illustrates the importance of factors other than pay, such as workplace composition, affecting behaviour. DePasquale and Stange () look at the effect of reducing regulation on the accreditation of foreign workers. They exploit the staggered adoption of the Nurse Licensure Compact (NLC), which made it easier for qualified nurses to practise in a different state to the one in which they qualified.…”
Section: Medical Labour Supplymentioning
confidence: 99%
“…Nursing is a licensed occupation in every state, hence it is reasonable to ask whether differences or changes in licensing requirements might play a role in a man’s decision to become an RN. DePasquale and Stange (2016) suggested that differences across states in licensing requirements for nurses in the period of our study are small and largely stable. Such requirements are therefore absorbed by state fixed effects in our models.…”
Section: Background: Historical Patterns Rn Training and Rn Relativmentioning
confidence: 80%